2017
DOI: 10.1049/iet-nbt.2016.0183
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of gold nanoparticles using Citrus maxima peel extract and their catalytic/antibacterial activities

Abstract: The peel of () is the primary byproducts during the process of fruit or juice in food industries, and it was always considered as biomass waste for further treatments. In this study, the authors reported a simple and eco-friendly method to synthesise gold nanoparticles (AuNPs) using peel extract as reducing and capping agents. The synthesised AuNPs were characterised by UV-visible spectrum, X-ray diffraction (XRD), transmission electron microscope (TEM) and Fourier-transform infrared spectroscopy (FTIR). The U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(29 citation statements)
references
References 49 publications
(52 reference statements)
7
20
0
1
Order By: Relevance
“…The diffraction peaks of 38.1° relates to (111), 44.5° relates to (200), 64.7° relates to (220), and 77.8° relates to (311) facets of the face center cubic (FCC) crystal lattice; these agree with reported values for similar gold nanostructures [ 69 ]. The reported peak values also matched the planes and face-centered cubic structures of AuNPs prepared by other green syntheses methods [ 22 , 70 , 71 , 72 ].…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…The diffraction peaks of 38.1° relates to (111), 44.5° relates to (200), 64.7° relates to (220), and 77.8° relates to (311) facets of the face center cubic (FCC) crystal lattice; these agree with reported values for similar gold nanostructures [ 69 ]. The reported peak values also matched the planes and face-centered cubic structures of AuNPs prepared by other green syntheses methods [ 22 , 70 , 71 , 72 ].…”
Section: Resultssupporting
confidence: 78%
“…However, the green synthesis of nanoparticles offers an alternative route utilizing the natural ingredients present in plant extracts from, for example, coriander, Bischofia javanica (L.), Daucus carota , Solanum lycopersicums , Hibiscus , cannabinus leaf, lemongrass, Moringa oliefera flower, Bacopa monnieri , Citrus unshiu peel, lemongrass ( Cymbopogon flexuosus ) [ 5 ], the plant extract of Aloe Vera leaves [ 6 ], and Ananas comosus [ 7 , 8 , 9 , 10 , 11 , 12 ]. There are several other published reviews reporting the green synthesis of different types of nanoparticles from plant extracts [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…peel, juice, etc.) of Citrus species mediated Ag‐NPs and Au‐NPs, our present study on CM‐AuNPs shows greater inhibition control of biofilm, even at a very low concentration ,,. Moreover, our results are promising and have higher inhibiting power compared to earlier reported nanoparticles,, in a similar period.…”
Section: Resultssupporting
confidence: 62%
“…This means that the plant extracts will contain different concentrations of natural reducing agents which can influence the characteristics of the nanoparticles. Green synthesized iron oxide nanoparticles from plants offers an alternative for exploitation of plants for pharmaceutical, water treatment, biomedical and catalytic applications [13][14][15][16][17]. Previous studies have shown that iron nanoparticles produced from plants have been used to catalyze the degradation of organic dyes such as bromothymol blue, methylene blue, aniline and Rhodamine B [14,18].…”
Section: Introductionmentioning
confidence: 99%